Mobile Ad Hoc Networks in Presence of Black Hole Attack - Anshu Prakash Murdan; Anshuman Bhowon (Institute of Advanced Engineering and Science, 2017)
This paper analyses three performance metrics namely average throughput, average network load and average video conferencing packet end-to-end delays under the influence of black hole attack in a Mobile Ad Hoc Network, using the ad hoc on-demand distance vector routing protocol. The simulation was carried out on Riverbed Modeler Academic Edition software. Simulation results show that the average throughput, average network load and average video conferencing packet end-to-end delay decreases as the number of black hole attack nodes is increased. Also, the effects of the influence of black hole attack nodes tend to decrease due to mobility of the nodes. It was observed that when the destination nodes move closer to the source nodes and get in to the latter’s transmission range, the effects of the black hole attack is greatly minimized.